If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 20 = 2x + 20 + -2r + -40 Reorder the terms: 20 + 3x = 2x + 20 + -2r + -40 Reorder the terms: 20 + 3x = 20 + -40 + -2r + 2x Combine like terms: 20 + -40 = -20 20 + 3x = -20 + -2r + 2x Solving 20 + 3x = -20 + -2r + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 20 + 3x + -2x = -20 + -2r + 2x + -2x Combine like terms: 3x + -2x = 1x 20 + 1x = -20 + -2r + 2x + -2x Combine like terms: 2x + -2x = 0 20 + 1x = -20 + -2r + 0 20 + 1x = -20 + -2r Add '-20' to each side of the equation. 20 + -20 + 1x = -20 + -20 + -2r Combine like terms: 20 + -20 = 0 0 + 1x = -20 + -20 + -2r 1x = -20 + -20 + -2r Combine like terms: -20 + -20 = -40 1x = -40 + -2r Divide each side by '1'. x = -40 + -2r Simplifying x = -40 + -2r
| 24+7=-4-9 | | -6b+2b-5b-3b+4b=18b | | y-5=0.11(x+9) | | 3n+7=82 | | 16=10-(4x+2) | | 5.34086e=231 | | -16t^2+80t+4=h(t) | | 4x=12+3x-x | | 1/2(6x-1/3) | | 72=-8m-24 | | 3x-43=2x-13 | | y-7=8(x-6) | | 3(x+5)=ex | | 2x+1=1-3x | | y+9=-5(x+6) | | 12x^2-26=x | | 72=-84-24 | | 0.3x^2-x=0 | | 7x-9*3=5x-6 | | y+10=7(x-9) | | -8+49r^2=-4 | | 8y-12=4y+8 | | y=85+10x | | -7=1-2b-2b | | 2(x+4)=5+2x | | 44=-7f-5 | | (4x+2)+(3x+19)=180 | | 4b-8=10-3b | | 0.33x^2-x=0 | | 10n+98=-872 | | 3=1/x | | -7(-1+5v)-5v=-39+6v |